Rancang Bangun Sistem Informasi Event Tracking Berbasis Web Bagi Pelaku Usaha UMKM Di Kota Pekanbaru - Rio Gusti Fauzi; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Micro, Small, and Medium Enterprises (MSME) in Pekanbaru City are an important part of the economy in Pekanbaru City. Development of the technology makes’ many people can buildtheir own business. Along with the number of businesses in Pekanbaru, many actors’ businesses are competing to promote and increase their businesses’ branding. One of the smartstrategies of MSME is to promote sales and increase profits through cooperation in events or exhibitions. This events can be a potential promotional field for the owners of Micro, Smalland Medium Enterprises or MSME. The system used to get information when the event will be performed by MSME in Pekanbaru is still using the traditional system by finding the events which organized by organizations or companies by MSME selves, mean while nowadays, thedevelopment of sophisticated technologies give many benefits. One of the benefits is to find every events information be easier. Therefore, the existence of Web-Based Event TrackingSystem Design for MSME actors’ businesses in Pekanbar is one way to facilitate MSME businesses to find the events information.Keywords : Information systems, website, event tracking, MSME